2015
DOI: 10.1309/ajcpgk8qtypuqjyl
|View full text |Cite
|
Sign up to set email alerts
|

Sporadic Fundic Gland Polyps With Low-Grade Dysplasia: A Large Case Series Evaluating Pathologic and Immunohistochemical Findings and Clinical Behavior

Abstract: Objectives: Fundic gland polyps (FGPs) occur in two clinicalFundic gland polyps (FGPs) are the most common type of gastric polyp. 1,2 They typically occur in the body and fundus of the stomach and are composed of cystically dilated oxyntic glands lined by attenuated chief, parietal, and mucous neck cells. The polyp surface is lined by gastric foveolar epithelium. FGPs occur in two different clinical settings, sporadic and syndromic (familial adenomatous polyposis, or FAP).Sporadic FGPs have been reported in 0.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 27 publications
1
35
1
Order By: Relevance
“…Dysplasia in d‐FGPs is generally described as occurring with surface foveolar and glandular mucous neck cells, with parietal and chief cells being uninvolved . In rare instances, dysplasia of parietal cells was hinted at but not definitely observed in our study, given the focal dysplasia within non‐foveolar, non‐mucous neck cells (Figure F) and possible nuclear β‐catenin staining within parietal cells (Figure C), although this was difficult to evaluate on IHC sections.…”
Section: Discussionmentioning
confidence: 58%
See 4 more Smart Citations
“…Dysplasia in d‐FGPs is generally described as occurring with surface foveolar and glandular mucous neck cells, with parietal and chief cells being uninvolved . In rare instances, dysplasia of parietal cells was hinted at but not definitely observed in our study, given the focal dysplasia within non‐foveolar, non‐mucous neck cells (Figure F) and possible nuclear β‐catenin staining within parietal cells (Figure C), although this was difficult to evaluate on IHC sections.…”
Section: Discussionmentioning
confidence: 58%
“…The development of malignancy in FGPs is extremely rare, with very few cases having been reported in the literature; it has been reported that FAP patients do not have an increased risk of gastric carcinoma . The adenomatous polyposis coli (APC)–β‐catenin pathway has been implicated in the development of dysplastic (and non‐dysplastic) FGPs in FAP patients, and immunohistochemistry (IHC) for β‐catenin can accordingly be positive in dysplastic nuclei …”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations